Doses de Bradyrhizobium japonicum e Azospirillum brasilense no desenvolvimento das plantas, na produção e na qualidade fisiológica de sementes de soja - Garcia, Ariani [UNESP] (2015)
Soybean (Glycine max (L.) Merrill) is one of the most important crops in the world economy. In Brazil, soybean inoculation with fixing bacteria atmospheric nitrogen is essential, and eliminates the need to additional fertilizers with nitrogen, generating savings of approximately $ 3 million for the country. Use of Azospirillum brasilense has been used in conjunction with Bradyrhizobium to optimize nodulation and generate positive responses in productivity and quality beans. Thus, the study aimed to evaluate the effects of doses of Bradyrhizobium japonicum and Azospirillum brasilense in plant development, production and physiological quality of soybean seeds. The study was conducted at UNESP experimental area - Ilha Solteira, located in Selvíria (MS), with experimental design of arranged randomized blocks in a 3x4 factorial design with four replications, in two soybean cultivars (TMG 1179RR and TMG 4182). The treatments were: Bradyrhizobium japonicum (without inoculation, 100 mL ha -1 and 200 mL ha -1 ) and Azospirillum brasilense (without inoculation, 100 mL ha -1, 200 mL ha -1 and 400 mL ha -1 ). Seeds were sown in December 2013, manually. They were analyzed: foliar nutritional content, root system, yield components, productivity and physiological quality of soybean seeds obtained. In conclusion: The Azospirillum brasilense increased the foliar content of calcium and nitrogen content and crude protein seed soy TMG 1179RR; inoculation of soybean isolated Azospirillum brasilense or co-inoculation significantly influences the performance of morphophysiological roots and provides increased nodulation by soybean plants; Azospirillum brasilense the use of co-inoculation with Bradyrhizobium japonicum at a dose of 200 mL ha -1 of each inoculant gave increase of 2,403.9 kg ha -1 in the yield of soybean cv. TMG 1179RR compared to the control (without inoculation of both); and that inoculation did not ...